Hydrodeoxygenation of fatty acid over La-modified HZSM5 for premium quality renewable diesel production - I. Nur Azreena; H.L.N. Lau; N. Asikin-Mijan; M.A. Hassan; S. Mohd Izham; M. Safa Gamal; Wan Nor Adira Wan Khalit; Mahashanon Arumugam; E. Kennedy; M. Stockenhuber; Yap, Taufiq Yun Hin (Elsevier, 2022)
In the present study, a series of La-HZSM5 catalysts were prepared through wet impregnation and investigated for the production of premium quality diesel fuel via hydrodeoxygenation (HDO) of oleic acid (OA). Several parameters were evaluated, such as reaction temperature (360–400 ◦C), H2 pressure (1–5 MPa), La concentration (5–20%), catalyst loading (1–7 wt%), and reaction time (1–4 h). At a reaction of 400 ◦C for 2 h under 5 MPa H2 pressure, the La(10)HZSM5(90) catalyst showed 97% hydrocarbon yield with 92% of diesel selectivity. The superior HDO activity by La(10)HZSM5(90) in producing high quality diesel is due to a sufficient number of weak + medium acid sites and its mesoporous structure. Vacuum distillation was complementary for producing high quality diesel fractions consisting of C17 fractions. The reusability of the La(10)HZSM5(90) catalyst was also demonstrated, though the catalyst still had coking activity.